A141 DUPILUMAB IMPROVES CLINICAL, SYMPTOMATIC, ENDOSCOPIC, AND HISTOLOGIC ASPECTS OF EOE, REGARDLESS OF PRIOR SWALLOWED TOPICAL STEROID USE. (7th March 2023) - Bredenoord, A J; Dellon, E S; Lucendo, A J; Collins, M H; Khodzhayev, A; Sun, X; Patel, K; Beazley, B; Shabbir, A
Abstract: Background: Swallowed topical corticosteroids (STC) are a first-line treatment for eosinophilic esophagitis (EoE) but are not uniformly effective. Dupilumab (DPL), a fully human monoclonal antibody, blocks the shared receptor component for IL-4/IL-13, key and central drivers of type 2 inflammation. In Parts A and B of the phase 3 LIBERTY-EoE-TREET (NCT03633617) study, weekly DPL 300mg improved clinical, symptomatic, histologic, and endoscopic aspects of EoE and was generally well tolerated in adult and adolescent patients (pts) with EoE. Purpose: To assess the efficacy of weekly DPL 300mg vs placebo (PBO) at Week 24 in pts from Parts A and B with/without prior history of STC use, and from Part B with/without a history of inadequate response, intolerance, or contraindication to STCs. Method: Pts who received STCs for EoE within 8 weeks prior to baseline were excluded from the study. Co-primary endpoints at Week 24 were the proportion achieving peak eosinophil count (PEC) ≤6/high-power field (hpf) and the absolute change in Dysphagia Symptom Questionnaire (DSQ) score. Other secondary endpoints at Week 24 included: % change in PEC; absolute change in Histologic Scoring System (HSS) grade and stage scores and Endoscopic Reference Score (EREFS); % change in DSQ score. Result(s): At baseline, in Parts A and B combined, 84/122 (69%) and 87/118 (74%) of DPL- and PBO-treated pts had history of STC use. For pts treated with DPL vs PBO PEC≤6/hpf was achieved by 59.5% vs 3.4% of pts with, and 57.9% vs 12.9% without, prior STC use. Difference vs PBO (95% CI) in the absolute change in DSQ score was −13.27 (−18.03, −8.50) vs −5.21 (−12.41, 2.00) for pts with/without prior STC use. Difference vs PBO (95% CI) for pts with/without prior STC use were: % change in PEC −80.76 (−97.77, −63.75)/−84.87 (−112.16, −57.58); absolute change in EoE-HSS grade −0.77 (−0.87, −0.66)/−0.57 (−0.77, −0.38) and stage −0.77 (−0.87, −0.66)/−0.55 (−0.73, −0.36); absolute change in EREFS −3.86 (−4.70, −3.02)/−2.59 (−4.16, −1.02); % change in DSQ −34.5 (−47.75, −21.22)/-14.9 (−35.21, 5.36). DPL was generally well tolerated in the intent-to-treat population; the most common TEAEs for DPL/PBO were injection-site reactions (37.7/33.3%). In Part B, 38/80 (48%) and 39/79 (49%) of DPL- and PBO-treated pts had inadequate response/intolerance/contraindication to STCs. For DPL vs PBO PEC≤6/hpf was achieved by 55.3% vs 7.7% with, and 61.9% vs 5.0% of pts without, inadequate response/intolerance/contraindication to STC. Difference vs PBO (95% CI) for absolute change in DSQ score was −11.55 (−19.06, −4.04)/−7.08 (−13.75, −0.42) for pts with/without inadequate response/intolerance/contraindication to STCs. Conclusion(s): Conclusion: Regardless of prior STC use, in this pooled analysis from Part A and Part B of the EoE TREET Phase 3 Study, weekly DPL 300mg demonstrated substantial improvements in clinical, histologic, and endoscopic study endpoints at Week 24 in adults and adolescents with EoE. Please acknowledge all funding agencies by checking the applicable boxes below: Other Please indicate your source of funding: Research sponsored by Sanofi and Regeneron Pharmaceuticals, Inc. Disclosure of Interest: A. Bredenoord Shareholder of: SST, Grant / Research support from: Bayer, Nutricia, SST, Consultant of: Arena Pharmaceuticals, AstraZeneca, Calypso Biotech, Dr Falk, EsoCap, Gossamer Bio, Laborie, Medtronic, RB Pharma, Regeneron Pharmaceuticals, Inc., Robarts Clinical Trials, E. Dellon Grant / Research support from: Research funding; Adare Pharma Solutions, Allakos, GSK, Meritage Pharma, Miraca Life Sciences, Nutricia, Receptos/BMS, Regeneron Pharmaceuticals, Inc., Shire. Educational grant; Allakos, Banner Pharmaceuticals, Holoclara, Consultant of: Abbott, Adare Pharma Solutions, Aimmune Therapeutics, Alivio Therapeutics, Allakos, Arena Pharmaceuticals, AstraZeneca, Banner Pharmaceuticals, Biorasi, Calypso Biotech, Enumeral, EsoCap, Gossamer Bio, GSK, Receptos/BMS, Regeneron Pharmaceuticals, Inc., Robarts Clinical Trials, Salix Pharmaceuticals, Shire/Takeda, A. Lucendo Grant / Research support from: Dr Falk, Regeneron Pharmaceuticals, Inc., Consultant of: Dr Falk, EsoCap, M. Collins Grant / Research support from: Receptos/BMS, Regeneron Pharmaceuticals, Inc., Shire, Consultant of: Allakos, AstraZeneca, BMS, EsoCap, Regeneron Pharmaceuticals, Inc., Shire, A. Khodzhayev Shareholder of: Regeneron Pharmaceuticals, Inc., Employee of: Regeneron Pharmaceuticals, Inc., X. Sun Shareholder of: Regeneron Pharmaceuticals, Inc., Employee of: Regeneron Pharmaceuticals, Inc., K. Patel Employee of: Sanofi, B. Beazley Shareholder of: Regeneron Pharmaceuticals, Inc., Employee of: Regeneron Pharmaceuticals, Inc., A. Shabbir Shareholder of: Regeneron Pharmaceuticals, Inc., Employee of: Regeneron Pharmaceuticals, Inc.